Factores socioculturales y violencia contra la mujer cocama en la comunidad nativa de Nueva Fortuna, distrito de Parinari 2023 - Vasquez Wong, Cesar Francisco (2024)
The research "Sociocultural Factors and Violence Against Cocama Women in the Native Community of Nueva Fortuna, Parinari District, 2023" aimed to understand the social factors that influence violence against Cocama women in the native community of Nueva Fortuna. The research followed a qualitative approach, descriptive research type, and ethnographic research design. It considered a population comprising 50% of the families of the total population, authorities, and key informants of the community. Techniques used included interviews and direct observation, with the interview guide as the instrument. Violence against women in communities like the native Cocama in Nueva Fortuna is influenced by various sociocultural factors and cultural practices that have been legitimized and/or normalized in violent ways against women, such as male control over family decisions and physical punishment as a method of discipline. The gender roles that are deeply rooted assign specific roles to men and women. Addressing violence against women in the native Cocama community of Nueva Fortuna requires a comprehensive approach that recognizes and respects cultural dynamics while promoting universal human rights and gender equality.